Efficient, Flexible and Secure Group Key Management Protocol for Dynamic IoT Settings - Kabra, Adhirath; Kumar, Sumit; S. Kasbekar, Gaurav (EAI Endorsed Transactions on Internet of Things, 2021)
For many Internet of Things (IoT) scenarios, group communication in the form of multicasting and broadcasting has proven to be effective. Classical Group Key Management (GKM) schemes perform inefficiently in dynamic IoT environments, wherein nodes frequently leave or join a network or migrate from one group to another. In this paper, we present a highly efficient and secure GKM protocol for dynamic IoT settings, which maintains forward and backward secrecy at all times and is completely resistant to collusion attacks. Also, our protocol is highly flexible and can handle several new scenarios in which device or user dynamics may take place, e.g., allowing a device group to join or leave the network or creation or dissolution of a user group, which are not handled by schemes proposed in prior work. We evaluate the performance of the proposed protocol via extensive mathematical analysis and numerical computations.
Keywords: Internet of Things; Sensors; Trust; Security and Privacy